2014
DOI: 10.1007/s12640-014-9466-z
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Derivative 2-(4′ Benzyloxyphenyl)-3-hydroxy-chromen-4-one Protects Against Aβ42-Induced Neurodegeneration in Transgenic Drosophila: Insights from In Silico and In Vivo Studies

Abstract: In the pathogenesis of Alzheimer's disease (AD), it is well established that the self-association of Aβ peptides into amyloid fibrils and/or plaque like aggregates causes neurotoxicity. As there is no cure for AD till date, identification of specific compounds that either inhibit the formation of Aβ-fibrils or help in the dissolution of already formed amyloid plaques makes an appealing therapeutic and preventive strategy in the development of drugs. In the present study, four synthetic flavonoid derivatives (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Nevertheless, due to their limited absorption and their low bioavailability in the brain, increasing evidence demonstrates that they are able to interact with the cellular and molecular components of the brain responsible for memory, having the potential to protect vulnerable neurons, enhance existing neuronal function, stimulate neuronal regeneration, and induce neurogenesis [ 194 , 195 ]. Recent study from our lab showed the neuroprotective property of a novel synthetic flavonoid derivative against A β -induce neurotoxicity in Drosophila model of AD [ 196 ].…”
Section: Neuroprotective Role Of Flavonoid Against Admentioning
confidence: 99%
“…Nevertheless, due to their limited absorption and their low bioavailability in the brain, increasing evidence demonstrates that they are able to interact with the cellular and molecular components of the brain responsible for memory, having the potential to protect vulnerable neurons, enhance existing neuronal function, stimulate neuronal regeneration, and induce neurogenesis [ 194 , 195 ]. Recent study from our lab showed the neuroprotective property of a novel synthetic flavonoid derivative against A β -induce neurotoxicity in Drosophila model of AD [ 196 ].…”
Section: Neuroprotective Role Of Flavonoid Against Admentioning
confidence: 99%
“…Several drug treatments are available to help prevent various symptoms in the disease, and researchers around the world are focusing on finding better treatments, preventive strategies, and ultimately a cure. Researchers are using different synthetic and/or herbal compounds to test their potential efficacy against AD [3][4][5][6]. In this milieu, polyphenolic compounds from medicinal plants are key sources of neuroprotective agents against AD.…”
Section: Introductionmentioning
confidence: 99%
“…Veber ( 31 ) demonstrated that molecules with TPSA≤140 Å 2 display efficient permeability. Higher partition coefficient log P will allow biologically active chloroacetamides higher efficiency by passive diffusion as well as effective binding to the active receptor sites ( 32 ). Besides, almost no divergence in log P (-Br, -CN) was observed for compounds with the same substituent in different positions ( 3 ).…”
Section: Discussionmentioning
confidence: 99%